2008
DOI: 10.1021/jp800775s
|View full text |Cite
|
Sign up to set email alerts
|

Ionization Spectroscopy of Conformational Isomers of Propanal: The Origin of the Conformational Preference

Abstract: Two different conformational isomers of propanal, cis and gauche, are investigated by the vacuum-UV mass-analyzed threshold ionization (VUV-MATI) spectroscopy to give accurate adiabatic ionization potentials of 9.9997 +/- 0.0006 eV and 9.9516 +/- 0.0006 eV, respectively. cis-Propanal, which is the more stable conformer in the neutral state, becomes less stable in the cation compared to gauche-propanal. Vibrational structures revealed in the MATI spectra indicate that cis and gauche isomers undergo their unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…It was reported that collision effect during expansion can result in exclusive formation of the most stable conformer. By changing the buffer gas from helium to argon, enhanced conformational cooling lead to exclusive formation of the cis conformational isomer of propanal over the gauche isomer [28]. The effect was explained with different collision cross-sections of collision gases.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that collision effect during expansion can result in exclusive formation of the most stable conformer. By changing the buffer gas from helium to argon, enhanced conformational cooling lead to exclusive formation of the cis conformational isomer of propanal over the gauche isomer [28]. The effect was explained with different collision cross-sections of collision gases.…”
Section: Resultsmentioning
confidence: 99%
“…MW=62.14, on the structure, oxygen atoms in the ethanol is substituted by sulfur atoms, then to obtain the compounds. The schematic structure of ethanethiol is shown in Fig.1, the structural formula is CH 3 CH 2 SH [1]. Ethanethiol is toxic [2] and oily liquid with achromatic color , transparent, volatile.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Sometimes a simple change of expansion gas can drastically change the distribution of conformations by relaxing the less stable conformers to the more stable ones. 18 There have been many studies on the relaxation between conformers. Rotational conformers of ethyl formate, ethanol, and isopropanol seeded in inert gases (He, Ne, Ar, and Kr) have been studied and it was found that those conformers with internal rotation barriers less than 400 cm À1 were efficiently relaxed.…”
Section: Introductionmentioning
confidence: 99%